Efectos del abono orgánico en el cultivo del maní arachis hypogaea en la granja Santa Ines - Vera Calderón, Fernando Patricio (2006)
In the farm Santa Inés of the University of Machala was investigated on the effects of the organic payments in the production of cultivating peanut, the outlined objectives were: 1. To determine the effectiveness of the organic payments in the peanut production. 2. To select the organic payment and the most appropriate dose. 3. To carry out the economic analysis of the results. The cultivated variety was the INIAP 381 and the studied treatments were: Biol 3000 and 4000 Lt/Ha; Humus, 4 -5 TM/Ha; Bokashi 2 and 3 TM/Ha; Compost 10 and 12 TM/Ha and the absolute witness. It lauds nine treatments they were assigned to parcels fixed at random in a Design Experimental Blocks with four repetitions, totalling 32 parcels. The organic payments incorporated to the floor before the seedtime and the Biol when the plants emerged and to the floweration. The cultivation was managed giving all the required cultural works; control of overgrowths, illnesses, and I water for furrows. The variables evaluated to determine the effect of the organic payments were: Days to the germination. Days to the floweration. Days to the maturation. Plant height to the 30,60 and 90 days after seedtime. Number of sheaths and grains for plant. I weigh of 100 seeds. Grain yield. The variance analyses and Test of multiple comparisons of the averages of treatments evidenced that the organic payments differ in quality in front of the macro readiness and micro available nutrients for the plants. The variety INIAP 381, it responded to the organic payment with bigger indexes of growth of the plants, production of sheaths and grains for plant, but at the end the Humus was superior as payment, giving the highest yields in 1842 and 1886 Kg/Ha, overcoming the witness in 82.9%. The biggest profitability in the cultivation and benefit cost was given in the treatment Humus 5TM/Ha.